Assessment of Stress Levels in Lactating Cattle: Analyzing Cortisol Residues in Commercial Milk Products in Relation to the Temperature-Humidity Index - Mohammad Ataallahi; Si Nae Cheon; Geun-Woo Park; Eska Nugrahaeningtyas; Jung Hwan Jeon; Kyu-Hyun Park (Animals, 2023)
Chronic stress in the dairy cattle industry has negative impacts on animal health, productivity, and welfare. It has been confirmed that cortisol transfers to milk and resists the high temperature during milk processing. This study evaluated the relationship between the milk cortisol concentration (MCC) in commercial milk products and the temperature-humidity index (THI) at the time of milk production. Eleven commercially produced pasteurized and sterilized milk products, purchased in Chuncheon, Korea, with production dates ranging from July to October 2021 were analyzed. The MCC was extracted using diethyl ether and analyzed using an enzyme immunoassay. The average THI values based on microclimate data provided by the Korea Meteorological Administration were 77 ± 0.8, 75 ± 1.4, 69 ± 1.4, and 58 ± 1.8, in July, August, September, and October, respectively. The average MCC levels were 211.9 ± 95.1, 173.5 ± 63.8, 109.6 ± 53.2, and 106.7 ± 33.7 pg/mL in July, August, September, and October, respectively. The MCC in July was higher than in August, September, and October (p < 0.05), while it was lower in September and October than in August (p < 0.05). Significant variations in the MCC were observed in commercial milk products across the four production months (p < 0.05), except for two milk products. Overall, monitoring the cortisol residue in commercial dairy milk products can be an alternative indicator of stress in dairy cattle of farms.